Essential Non-coding Genes: A New Playground of Bioinformatics - Zhang, Ying-Ying; Du, Pu-Feng (Current Bioinformatics, 2023)
The essentiality of a gene can be defined at different levels and is context-dependent. Essential protein-coding genes have been well studied. However, the essentiality of non-coding genes is not well characterized. Although experimental technologies, like CRISPR-Cas9, can provide insights into the essentiality of non-coding regions of the genome, scoring the essentiality of noncoding genes in different contexts is still challenging. With machine learning algorithms, the essentiality of protein-coding genes can be estimated well. But the development of these algorithms for non-coding genes was very early. Based on several recent studies, we believe the essentiality of noncoding genes will be a new and fertile ground in bioinformatics. We pointed out some possible research topics in this perspective article.
Keywords: non-coding genes